Apollinaire, ou la double tentation de la solitude et de l’autre - Luca Bevilacqua (Revue Italienne d'Etudes Françaises)
Sensitive to the various calls from the past (classical culture, the Middle Ages, symbolist poetry) and the present (the avant-garde, the press, advertising), Apollinaire reveals to us throughout his work a great richness not devoid of ambiguities. Besides the famous antagonism between Order and Adventure, another obvious contradiction concerns the scope of the audience he addresses: while some of his poems are very accessible and imbued with musicality, in other cases, he seems to write only for cultured readers. Apollinaire often emphasizes his condition as a poet-prophet and the solitude of his quest, while paradoxically assuming the role of a cultural mediator through numerous articles on contemporary art and literature. The study presented here attempts to analyze these contradictions, particularly the one between the quest for the approval of others (the temptation of the other) and the need for intimacy (the ivory tower).